Factors Affecting Early Retirement Intentions With the Mediating Mechanism of Job Engagement - Khan, Asfand Yar; Bilal, Dr. Atif; Daud, Nadia; Daniyal, Muhammad; Ahmed, Bilal; Ishaq, Atiq (Master in Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2024)
The main objective of this study is to empirically examine the associations between work goals (intrinsic and extrinsic) and early retirement intentions, with the mediating mechanism of work passion and the moderating role of flexible HR practices, spouse’s health, and position level (employees’ position level in organizations, e.g., junior manager at lower level, deputy manager at middle level, or senior manager at upper level etc.). Data for the study was collected through survey-based questionnaires distributed to a sample of 350 female employees from different public and private sector organizations in Pakistan. Testing of the hypotheses was conducted using structural equation modeling (SEM) with WarpPLS software. The findings indicate that employees’ work goals are positively related to the level of passion they feel about their work. However, this has a negative impact on their early retirement intentions. Besides, the results show that this work passion mediates the relationship between work goals and early retirement intentions. Furthermore, flexible HR practices, position level, and spouse’s health moderate the relationship between work passion and early retirement intentions. The study’s theoretical and managerial contributions and limitations are also discussed at the end of the article.